PELATIHAN PENDIDIKAN SEKS PADA ANAK USIA DINI DENGAN METODE PRETEND PLAY - Alucyana; Raihana; Dian Tri Utami (Kreasi: Jurnal Pengabdian Masyarakat, 2021)
Today, more and more cases of sexual abuse of children. Sexual harassment can result in typical post-traumatic psychological symptoms. There are so many psychological impacts on child victims of rape, it is necessary to provide healing, one of which is sex education. Sex education is intended so that children can understand the condition of their own bodies and bodies of the opposite sex, and are able to teach children to be able to avoid sexual violence. One of the effective methods used in early childhood sex education is the pretend play method. The result of this activity is a change in understanding about the importance of sex education in early childhood, as well as new skills in methods for sex education in early childhood.